An empirical phenomenological investigations of the experience of being unemployed : a critical study in the South African context - Jaffray, Timothy William (Rhodes University, Faculty of Humanities, Department of Psychology, 1990)
Unemploynent is a problem that confronts many western countries. The aim of this dissertation is to understand, on the basis of a phenomenological investigation, what it means to be an unemployed, white, South African citizen. These meanings are then seen and discussed against the background of the problems associated with the ideological structure within the country. How the latter relates to white employment and psychological life is also explored. The results demonstrate the negative impact unemploynent has upon the psychological functioning of the individual. The results further show the despair such individuals face, having been 'denied' an accepted role within society.
Keywords: Unemployment -- Psychological aspects; Unemployment -- South Africa -- Psychological aspects